Obesity promotes liver carcinogenesis via Mcl-1 stabilization independent of IL-6Rα signaling - Gruber, Sabine; Straub, Beate Katharina; Schirmacher, Peter (Cell reports, 2013)
Obesity increases the incidence of hepatocellular carcinoma (HCC) development in part through the activation of obesity-associated proinflammatory signaling. Here, we show that in lean mice, abrogation of IL-6Rα signaling protects against diethylnitrosamine (DEN)-induced HCC development. HCC protection occurs via Mcl-1 destabilization, thus promoting hepatocyte apoptosis. IL-6 regulates Mcl-1 stability via the inhibition of PP-1α expression, promoting GSK-3β inactivation. In addition, IL-6 suppresses expression of the Mcl-1 E3 ligase (Mule). Consequently, IL-6Rα deficiency activates PP-1α and Mule expression, resulting in increased Mcl-1 turnover and protection against HCC development. In contrast, in obesity, inhibition of PP-1α and Mule expression, leading to Mcl-1 stabilization, occurs independently of IL-6 signaling. Collectively, this study provides evidence that obesity inhibits hepatocyte apoptosis through Mcl-1 stabilization independent of IL-6 signaling, thus promoting liver carcinogenesis.
Im Titel wird alpha als griechischer Buchstabe dargestellt
Gesehen am 29.01.2021